Factors Influencing Forensic Accounting services Awareness In Iraqi environment - Naseem Yousuif Al Lallo (مجلة الغري للعلوم الاقتصادية والادارية, 2022)
Forensic accounting considered as modern tools to address fraud and corruption crimes in countries that suffering from this phenomena. There are many services that Forensic Accounting provided. In Iraq there is low level of awareness related to Forensic accounting services. This study was a theoretical attempt to declare the factors that influence on Forensic Accounting Services Awareness (FASA). Current study found that there five factors which they are: Professional bodies, Accounting firms, Multimedia, Government, Education, these factors affected on FASA and they are suitable for the Iraqi environment.